Thiacalix[4]arene-supported molecular clusters for catalytic applications. Issue 11 (2nd March 2021) - Hang, Xinxin; Bi, Yanfeng
Abstract : Recent advances of thiacalix[4]arene-supported molecular clusters for catalytic applications are presented. Abstract : Thiacalixarenes are intriguing ligands that have attracted sustained interest because of their changeable conformations and excellent coordination ability. Thiacalix[4]arene analogues, which can bind metal ions to form modular second building units, are capable of constructing molecular-based functional materials with defined structures and various applications via directional coordination assembly. Due to rich metal–sulfur bonds, thiacalix[4]arene-based molecular clusters also exhibit diverse properties compared to other clusters. In particular, the combination of thiacalixarenes with currently popular molecular architectures, such as high-nuclearity clusters and coordination cages, has shown special catalytic performances. In this perspective, the latest advances in catalytic applications of thiacalix[4]arene-based molecular clusters, including molecular clusters themselves as catalysts and coordination cages serving as reaction vessels encapsulating metal nano-components for catalysis, are highlighted.